A fiber array-based radiation cooling surface and its preparation method and application

By using a fiber -based structure in the radiation refrigeration material, the combination of static fleece technology and polymer matrix and inorganic filler particles is used to solve the problem of complex and high cost preparation technology of the existing materials. Essence

CN114659290BActive Publication Date: 2025-01-28THE NAT CENT FOR NANOSCI & TECH NCNST OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210291153.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-23
Publication Date
2025-01-28
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

The existing radiation refrigeration materials are complex and expensive in the preparation process, and porous materials have problems such as poor adhesion and insufficient weather resistance.

Method used

The radiation refrigeration surface based on a fiber array is adopted, and the top fiber array structure is built on the bottom glue layer through electrostatic velvet technology. The combination of high -molecular matrix, inorganic filler particles and curing agents can be used to achieve high reflection rates and high emission rates.

Benefits of technology

The high visible light reflectance and medium -infrared high emission rate are achieved, reducing the preparation cost and process complexity, and at the same time improve the adhesion and weather resistance, which can achieve a cooling temperature difference of 9 ° C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114659290B_ABST
    Figure CN114659290B_ABST
Patent Text Reader

Abstract

The present invention provides a fiber array-based radiation cooling surface and a preparation method and application thereof. The fiber array-based radiation cooling surface includes a bottom glue layer and a top fiber array structure; the preparation raw materials of the bottom glue layer include a polymer matrix, inorganic filler particles and a curing agent. The fiber array-based radiation cooling surface provided by the present invention has a series of advantages such as high solar reflectivity, high mid-infrared emissivity, and strong adhesion to the substrate, and has excellent radiation cooling performance. The fiber array-based radiation cooling surface provided by the present invention can be used for building exterior walls, thermal control mechanisms, etc. to adjust the internal temperature. In addition, the fiber array-based radiation cooling surface provided by the present invention has a simple preparation process and low cost, and is suitable for large-scale production and preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of radiation cooling, and relates to a radiation cooling surface based on a fiber array, and a preparation method and application thereof. Background Art

[0002] Radiative cooling is a common natural phenomenon. Radiative cooling materials refer to a type of material that uses its own outward thermal radiation to transfer heat and reduce its own temperature. According to Planck's law of thermal radiation, any object has radiation characteristics and radiates energy to the outside world all the time. The temperature of space outside the atmosphere is extremely low, which provides an ideal cold source for radiative cooling. However, not all materials can become radiative refrigerators, because the earth is surrounded by the atmosphere, and most wavelengths of infrared radiation will be absorbed by the atmosphere, and this part of energy will be returned to the object through radiation, so radiative cooling cannot be achieved. However, in the atmospheric transmission spectrum, the mid-to-far infrared band at 8-13μm has extremely high transmittance. Electromagnetic waves in this band can pass through the atmosphere to reach outer space and are almost not absorbed. Therefore, this band is called the atmospheric transparent window. If a material has a strong radiation ability in the atmospheric transparent window area, radiative cooling can be achieved.

[0003] Radiative cooling can be divided into nighttime radiative cooling and daytime radiative cooling. At night, there is no solar radiation, and objects have strong radiation ability in the atmospheric window zone, which can achieve radiative cooling; during the day, objects are irradiated by sunlight. The sun continuously radiates heat to the earth's surface. According to the solar spectrum irradiance distribution map, the solar radiation that the earth's surface can receive is mainly concentrated in the visible light region (400-700nm) and the near-infrared region (700-2500nm). Therefore, there are two key factors to achieve daytime radiative cooling: (1) high emissivity in the atmospheric window zone; (2) high reflectivity to sunlight in the visible light region and near-infrared region.

[0004] In nature, some insects have special hair-like structures on their outer shells that enhance their ability to reflect sunlight and emit infrared light. The Saharan silver ant is a typical biological example of daytime radiative cooling (SHI NN, TSAI CC, CAMINO F, et al. 2015. Keeping cool: Enhanced optical reflection and radiative heat dissipation in Saharan silver ants. Science [J], 349: 298). The Saharan silver ant is a type of ant that lives in the Sahara Desert and often travels in temperatures of 47°C. The dense array of unique triangular prism hairs on the ants enhances solar reflection and infrared emission. Moreover, the triangular prism shape of the hair can fully reflect, increase its reflectivity, and help the silver ants stay cool. Similarly, the wing hairs of long-horned beetles also have excellent temperature regulation functions (ZHANG H, LY KCS, LIU X, et al. 2020. Biologically inspired flexible photonic films for efficient passive radiative cooling. Proc Natl Acad Sci USA[J], 117: 14657-14666). So far, there have been no reports on the preparation of radiative cooling surfaces by imitating the structure of insect epidermal hairs.

[0005] The radiation cooling materials reported so far are roughly divided into optical thin film devices, metamaterials, porous materials and fiber fabrics. Optical thin film devices are composed of multiple dielectric layers with a thickness of nanometers. Through the combination of dielectric layer material types and thickness changes, the light passing through its structure produces interference enhancement or destructive phenomena, thereby achieving precise control of the reflection, transmission and absorption of incident light. In 2014, Professor Fan Shanhui of Stanford University published a breakthrough result of photonic crystal radiation cooler (RAMAN AP, ANOMA MA, ZHU L, et al. 2014. Passive radiative cooling below ambient air temperature under direct sunlight. Nature [J], 515: 540-544). The film layer is composed of seven HfO2 and SiO2 film layers of different thicknesses alternately stacked. The superposition of the first three layers of HfO2 and SiO2 with different thicknesses is a combination of material properties and interference effects to increase the radiation in the mid-infrared region; the bottom four layers are used to help improve the reflectivity of the solar spectrum. Similarly, CN112984857A discloses a radiative cooling multilayer film structure that can present structural colors. In terms of metamaterials, in 2010, AR Gentle et al. of the University of Technology Sydney proposed to prepare a new metamaterial by embedding nano-sized SiC and SiO2 spheres into polyethylene film to achieve effective radiative cooling (GENTLE AR, SMITH G B2010. Radiative heat pumping from the Earth using surface phonon resonant nanoparticles. Nano Lett [J], 10: 373-379); in 2015, Min Gu et al. of Swinburne University of Technology, Australia, designed and prepared a metamaterial composed of a series of symmetrical conical microstructures (HOSSAIN MM, JIA B, GUM 2015. A Metamaterial Emitter for Highly Efficient Radiative Cooling. Advanced Optical Materials [J], 3: 1047-1051).In terms of porous materials, in 2018, Yu Nanfang's team prepared a multi-scale micro-nano porous polymer film material (MANDAL J, FU Y, OVERVIG AC, et al. 2018. Hierarchically porous polymer coatings for highly efficient passive daytime radiative cooling. Science [J], 362: 315). The film material is composed of PVDF-HFP, with a solar reflectivity of 0.96 and an atmospheric window emissivity of 0.97. In addition, CN113136724A announced a radiative cooling fabric with a solar reflectivity of 0.95.

[0006] In summary, there are many types of radiation cooling materials, and the principles and preparation methods are also different. However, if they are to be truly applied in practice, there are still some problems to be solved: the preparation process of one-dimensional photonic crystals and metamaterials often involves micro-nano processing methods such as surface evaporation and etching, which is complicated and expensive, limiting large-scale applications. Porous radiation cooling materials or fiber fabrics usually have disadvantages such as poor weather resistance and poor adhesion.

[0007] Therefore, it is necessary to develop a new type of radiative cooling surface with simple preparation method, low cost and able to adapt to practical application needs. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a fiber array-based radiation cooling surface and its preparation method and application. The fiber array-based radiation cooling surface provided by the present invention solves the drawbacks of other types of radiation cooling materials in the prior art (such as the complex and expensive preparation process of optical films and metamaterials; the poor adhesion and thick porous materials, etc.), and at the same time improves the disadvantage of low infrared emissivity in traditional high-reflection surfaces.

[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a fiber array-based radiative cooling surface, wherein the fiber array-based radiative cooling surface comprises a bottom glue layer and a top fiber array structure;

[0011] The raw materials for preparing the bottom glue layer include a polymer matrix, inorganic filler particles and a curing agent.

[0012] The fiber array-based radiation cooling surface provided by the present invention has the advantages of high visible light reflectivity, high mid-infrared emissivity, good adhesion, etc., and the preparation method is simple and the cost is low.

[0013] Preferably, the polymer matrix includes any one of silicone rubber, epoxy resin or fluorocarbon resin or a combination of at least two thereof, preferably silicone rubber.

[0014] As a preferred technical solution of the present invention, the selection of the curing agent matches the polymer matrix used. For example, when the polymer matrix is ​​silicone rubber, the curing agent used is silicone rubber, and when the polymer matrix is ​​epoxy resin, the curing agent used is epoxy resin curing agent.

[0015] Preferably, the inorganic filler particles are highly reflective inorganic filler particles.

[0016] Preferably, the inorganic filler particles include any one of SiO2, Al2O3, rutile TiO2 or BaSO4 or a combination of at least two thereof, preferably rutile TiO2. Sunlight is incident on the surface of the adhesive layer, and is reflected by Mie scattering (Mie scattering) of the filler particles. Furthermore, by changing the particle size and mass fraction of the filler particles, the Mie scattering behavior can be regulated, so that the adhesive layer has a higher reflectivity in the visible and near-infrared regions.

[0017] Preferably, the diameter of the inorganic filler particles is 50-500 nm, for example, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.

[0018] Preferably, the diameter of the SiO2 is 100-300nm, for example, 100nm, 150nm, 200nm, 250nm or 300nm.

[0019] Preferably, the diameter of the Al2O3 is 200-400nm, for example, 200nm, 250nm, 300nm, 350nm or 400nm.

[0020] Preferably, the diameter of the rutile TiO2 is 200-400nm, for example, 200nm, 250nm, 300nm, 350nm or 400nm.

[0021] Preferably, the diameter of the BaSO4 is 100-300 nm, for example, 100 nm, 150 nm, 200 nm, 250 nm or 300 nm.

[0022] The diameter of the rutile TiO2 of the present invention is preferably 200-400nm. According to Mie scattering theory, when the diameter of rutile TiO2 nanoparticles is 200-400nm, the scattering efficiency peak value is obtained in the 400-800nm ​​wavelength region, corresponding to the best reflection ability in this wavelength range, and this wavelength range is the area where the sunlight energy is most concentrated, so the rutile TiO2 particles of this diameter can obtain the highest sunlight reflectivity. When the diameter of rutile TiO2 particles decreases, the scattering efficiency peak value blue-shifts; when the diameter of rutile TiO2 particles increases, the scattering efficiency peak value red-shifts, and the highest scattering efficiency cannot be obtained in the band with the strongest solar radiation, and the reflection ability to sunlight will be reduced.

[0023] Preferably, the mass ratio of the inorganic filler particles to the matrix is ​​3:10-4:10, such as 3:10, 3.2:10, 3.4:10, 3.6:10, 3.8:10 or 4:10, etc. If too many inorganic filler particles are added, the bottom glue layer will become sticky, and it will be difficult to make the fibers fly up and insert during the flocking process; if too few inorganic filler particles are added, sunlight cannot be effectively reflected.

[0024] Preferably, the mass ratio of the curing agent to the matrix is ​​1:10-2:10.

[0025] Preferably, the thickness of the bottom glue layer is 50-500 μm, such as 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm, etc., preferably 100-200 μm. If the bottom glue layer is too thin, it is difficult to achieve high reflection of sunlight, and the fibers cannot be inserted and fixed during the flocking process; if the bottom glue layer is too thick, the fibers are easy to fall over or even sink during the flocking process, and a good array structure cannot be formed. If the glue layer is too thick, it is easy to fall off after curing, and the mechanical properties of the surface are reduced.

[0026] Preferably, the top fiber array structure consists of white polymer fibers.

[0027] Preferably, the top fiber array structure is composed of white nylon fibers.

[0028] Preferably, the white nylon fiber has a diameter of 5-15 μm, such as 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, and a length of 400-600 μm, such as 400 μm, 450 μm, 500 μm, 550 μm or 600 μm.

[0029] Preferably, the surface density of the top fiber array structure is 10-100 g / m 2, for example 10g / m 2 , 20g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 or 100g / m 2 etc., preferably 20-40g / m 2 .

[0030] The short fibers are inserted vertically into the bottom glue layer through the electrostatic flocking process to form a fiber array structure similar to insect hair. The characteristic dimensions of this structure (fiber diameter and surface density of the fiber array structure) are comparable to the wavelength of infrared light, and can be used as a gradient refractive index layer to significantly improve its absorptivity and emissivity in the mid-infrared atmospheric window region.

[0031] Furthermore, silicone rubber is selected as the polymer matrix of the bottom adhesive layer. Silicone rubber has a very low extinction coefficient in the visible light band and absorbs almost no visible light energy; but at the same time, it has a strong absorption peak in the mid-infrared band of 8-13μm, making it a typical polymer material with low absorption of sunlight and high emission of infrared light. The curing conditions of silicone rubber are mild, the cured product is soft, and has good adhesion to the substrate.

[0032] Rutile TiO2 is selected as the inorganic filler particles. Rutile TiO2 nanoparticles have a high refractive index in the visible light band, which makes TiO2 have a strong reflective ability to visible light; at the same time, the absorption peak only appears in the ultraviolet light band below 400nm, and the energy of the ultraviolet light band only accounts for about 5% of the total energy of sunlight. Therefore, rutile TiO2 is an excellent sunlight reflective material. Compared with ordinary TiO2, rutile TiO2 has a higher refractive index in the visible light band.

[0033] White nylon fibers are selected to form the fiber array structure. After bleaching, the nylon fibers are pure white and have a high reflectivity in the visible light region. At the same time, due to their own chemical structure, they can also absorb and emit infrared light well in the mid-infrared region.

[0034] In a second aspect, the present invention provides a method for preparing the fiber array-based radiation cooling surface according to the first aspect, the preparation method comprising the following steps:

[0035] The top fiber array structure is constructed on the bottom glue layer by electrostatic flocking and solidified to obtain the fiber array-based radiation cooling surface.

[0036] Preferably, the bottom glue layer is prepared by the following method:

[0037] The polymer matrix, inorganic filler particles and curing agent in the prescribed amount are mixed and dispersed to obtain a mixed liquid, and then the mixed liquid is coated on the substrate to obtain the bottom glue layer.

[0038] Preferably, the mixing and dispersing is vacuum degassing and stirring.

[0039] Preferably, the specific process of vacuum degassing and stirring is: stirring at a rate of 500-1000r / min (e.g., 500r / min, 600r / min, 700r / min, 800r / min, 900r / min or 1000r / min, etc.) for 5-10min (e.g., 5min, 6min, 7min, 8min, 9min or 10min, etc.) at normal pressure, and then at 20-60kPa (e.g., 20kPa, 30kPa, 40kPa, 5 The mixture is stirred at a rate of 1500-2500 r / min (e.g. 1500 r / min, 1600 r / min, 1700 r / min, 1800 r / min, 1900 r / min, 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min or 2500 r / min, etc.) for 3-5 min (e.g. 3 min, 4 min or 5 min, etc.) under a vacuum degree of 0 kPa or 60 kPa, etc.

[0040] Preferably, the coating method includes spraying or scraping.

[0041] Preferably, the spraying includes spraying with a spray gun with a caliber of 0.3-0.8mm (for example, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm or 0.8mm, etc., preferably 0.5mm) or a spray pen with a caliber of 0.3-0.8mm (for example, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm or 0.8mm, etc., preferably 0.5mm).

[0042] Preferably, the scraping includes scraping with a four-corner coater.

[0043] The present invention does not limit the specific selection of the substrate, which only serves to support the bottom adhesive layer. For example, the substrate may be an aluminum foil.

[0044] Preferably, the process of constructing the top fiber array structure on the bottom glue layer by electrostatic flocking is:

[0045] Fix the bottom glue layer on the metal upper plate, disperse the white polymer fibers on the metal lower plate, turn on the DC high-voltage power supply, and the white polymer fibers will rise vertically under the action of the electrostatic field and insert into the bottom glue layer.

[0046] Preferably, the fixing comprises fixing with tape.

[0047] Preferably, the dispersing comprises dispersing using a vibrating screen.

[0048] Preferably, the distance between the upper electrode plate and the lower electrode plate is 10-30 cm, such as 10 cm, 15 cm, 20 cm, 25 cm or 30 cm, etc., preferably 10 cm.

[0049] Preferably, the voltage of the DC high-voltage power supply is 5-40kV, for example 5kV, 10kV, 15kV, 20kV, 25kV, 30kV, 35kV or 40kV, etc., preferably 30-35kV, and the power-on time is 5-20s, for example 5s, 10s, 15s or 20s, etc., preferably 10s.

[0050] If the electric field strength is too large, the fibers will easily connect during the flying process, forming a pathway and causing discharge; if the electric field strength is too small, it will not be enough to make the fibers fly, or the flying speed will be too slow to be inserted into the glue layer.

[0051] Preferably, the curing temperature is 80-100°C, such as 80°C, 85°C, 90°C, 95°C or 100°C, etc., preferably 80°C, and the curing time is 2-3h, such as 2h, 2.5h or 3h, etc., preferably 2h.

[0052] Preferably, the curing is carried out in an oven.

[0053] Preferably, after curing, the method further includes a step of blowing and cleaning with a high-pressure air gun to remove residual dust and fibers.

[0054] As a preferred technical solution of the present invention, the method for preparing the fiber array-based radiation cooling surface comprises the following steps:

[0055] (1) mixing and dispersing a polymer matrix, inorganic filler particles and a curing agent in a prescribed amount to obtain a mixed solution, and then coating the mixed solution on a substrate by spraying or scraping to obtain the bottom adhesive layer;

[0056] (2) fixing the bottom glue layer on the metal upper electrode plate, dispersing the white polymer fibers on the metal lower electrode plate, turning on the DC high-voltage power supply, and the white polymer fibers vertically rise under the action of the electrostatic field and are inserted into the bottom glue layer to obtain a bottom glue layer with a fiber array structure attached; wherein the distance between the upper electrode plate and the lower electrode plate is 10-30 cm, the voltage of the DC high-voltage power supply is 5-40 kV, and the power-on time is 5-20 s;

[0057] (3) Curing the bottom adhesive layer with the fiber array structure attached in step (2) at 80-100° C. for 2-3 hours to obtain the fiber array-based radiation cooling surface.

[0058] In a third aspect, the present invention provides an application of the fiber array-based radiation cooling surface according to the first aspect in refrigeration and temperature reduction.

[0059] The parameters for measuring the performance of the fiber array-based radiation cooling surface include cooling temperature difference, cooling power density, etc. Cooling power density refers to the net power of the material to achieve cooling per unit area, that is, the energy reduced per unit area and per unit time; cooling temperature difference refers to the temperature difference between the material and the reference sample, which can usually intuitively reflect the radiation cooling effect of the material.

[0060] Preferably, the refrigeration and cooling includes at least one of being used for sun protection and cooling of building exterior walls or vehicles, aerospace thermal control equipment, and condensation of outdoor water collection devices.

[0061] The cooling principle of the fiber array-based radiation cooling surface of the present invention is: the inorganic filler particles in the bottom silicone rubber can effectively reflect sunlight through Mie scattering, preventing the energy radiated by the sun from passing through the surface and entering the interior; the fiber array-like structure on the top is similar to the hair of Saharan silver ants. Since the characteristic size is comparable to the wavelength of mid-infrared light, it is equivalent to forming a layer of gradient refractive index layer between the bottom glue layer and the external air, which can effectively improve the surface's absorption and emission capabilities in the mid-infrared region, so that more energy can be emitted to the outside world through the atmospheric window in the form of thermal radiation. Therefore, the fiber array-based radiation cooling surface of the present invention reduces the energy entering from solar radiation through the high reflectivity of the sunlight area, and increases the energy radiated to the outside world through the high emissivity of the mid-infrared atmospheric window area, so as to achieve the purpose of reducing its own energy and achieve the effect of cooling.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] (1) The present invention provides a radiation cooling surface based on a fiber array. The average reflectivity of the radiation cooling surface based on the fiber array is more than 97% in the visible light region, and the average emissivity in the mid-infrared atmospheric window region is more than 95%. While ensuring high reflectivity in the sunlight region, it also achieves high emissivity in the mid-infrared region, overcoming the defect that traditional surfaces cannot take both into account. It can effectively reflect most of the sunlight, and at the same time, it can emit a large amount of its own energy outward in the form of thermal radiation, and can achieve a cooling temperature difference of 9°C.

[0064] (2) The present invention adopts a spraying or scraping method to prepare the bottom adhesive layer, and then uses an electrostatic flocking method to construct a fiber array structure on the adhesive layer. Compared with radiation cooling materials such as photonic films, the present invention has a simple process, low cost, and is suitable for large-area preparation. It also overcomes the shortcomings of radiation cooling materials such as aerogels and porous materials, which are too thick and have poor adhesion to the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 A schematic structural diagram of a fiber array-based radiation cooling surface provided in Example 1 of the present invention.

[0066] Among them, 1-bottom adhesive layer, 2-top fiber array structure, 3-sunlight reflection, 4-mid-infrared light reflection.

[0067] Figure 2 This is a front SEM image of the fiber array-based radiative cooling surface provided in Example 1 of the present invention.

[0068] Figure 3 This is a cross-sectional SEM image of the fiber array-based radiative cooling surface provided in Example 1 of the present invention.

[0069] Figure 4 This is a reflectivity graph in the ultraviolet-visible-near infrared region of the fiber array-based radiative cooling surface provided in Example 1 of the present invention.

[0070] Figure 5 This is a mid-infrared emissivity diagram of the fiber array-based radiation cooling surface provided in Example 1 of the present invention.

[0071] Figure 6 This is a graph of the outdoor measured temperature drop of the fiber array-based radiative cooling surface provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Example 1

[0074] In this embodiment, a radiation cooling surface based on a fiber array is provided (the structural schematic diagram is shown in FIG. Figure 1 As shown), the fiber array-based radiation cooling surface includes a bottom glue layer 1 and a top fiber array structure 2. The raw materials for preparing the bottom glue layer include rutile TiO2 nanoparticles, silicone rubber and silicone rubber curing agent in a mass ratio of 4:10:1, the diameter of the rutile TiO2 nanoparticles is 230nm, the model of the silicone rubber and the silicone rubber curing agent is Sylgard 184, and the thickness of the bottom glue layer is 150μm; the top fiber array structure is composed of white nylon fibers, the diameter of the white nylon fibers is 14μm, the length is 400-600μm, and the surface density of the top fiber array structure is 20g / m 2 .

[0075] The fiber array-based radiation cooling surface of this embodiment is prepared by the following method:

[0076] (1) Weighing 2 g of rutile TiO2 nanoparticles, 5 g of silicone rubber, and 0.5 g of silicone rubber curing agent, placing them in a vacuum degassing mixer and stirring them at a rate of 800 r / min for 5 min at normal pressure, and then stirring them at a rate of 2000 r / min for 3 min at a vacuum degree of 30 kPa to obtain a mixed solution, and then using a four-corner coater to scrape the mixed solution onto an aluminum foil substrate of 10 cm*10 cm in size to obtain the bottom adhesive layer;

[0077] (2) The bottom adhesive layer is evenly attached to the metal upper plate with paper tape and connected to the negative pole of the power supply. The white nylon fiber is evenly spread on the metal lower plate connected to the positive pole of the power supply with a vibrating screen. The amount of white nylon fiber added is controlled so that the surface density of the final fiber array is 20g / m 2 , turn on the DC high-voltage power supply, the white polymer fiber rises vertically under the action of the electrostatic field and is inserted into the bottom glue layer, obtaining a bottom glue layer with a fiber array structure attached; wherein, the distance between the upper electrode plate and the lower electrode plate is 10 cm, the voltage of the DC high-voltage power supply is 30 kV, and the power-on time is 10 s;

[0078] (3) Turn off the high-voltage power supply, carefully take out the metal upper electrode plate, put it into an oven and keep it at 80° C. for 3 hours to cure the silicone rubber, take out the cured material, and blow and clean it with a high-pressure air gun to obtain the fiber array-based radiation cooling surface.

[0079] The following tests were performed on the fiber array-based radiative cooling surface prepared in this embodiment:

[0080] (1) The surface morphology of the prepared fiber array-based radiative cooling surface was analyzed using a scanning electron microscope (Hitachi S4800);

[0081] (2) The reflectivity of the prepared fiber array-based radiative cooling surface in the solar wavelength band was tested using a UV-visible-near infrared spectrophotometer (Agilent Cary7000) equipped with an integrating sphere accessory;

[0082] (3) A Fourier transform infrared spectrometer (Bruker Vertex80V) equipped with an integrating sphere accessory was used to test the emissivity of the prepared fiber array-based radiation cooling surface in the mid-infrared band;

[0083] (4) The outdoor performance of the prepared fiber array-based radiant cooling surface was measured. The aluminum foil samples coated with the surface and the uncoated surface were placed in insulation boxes of the same size and material. A 10cm*10cm hole was opened on the top of the insulation box and sealed with the sample, so that the coated surface was facing up to reflect sunlight. Thermocouples were attached to the bottom surfaces of the two samples respectively, and data loggers were connected to record the temperatures of the two in real time. At the same time, the real-time weather conditions were recorded through a small weather station. The greater the temperature difference, the better the cooling effect. The thermocouple used was an Omega K-type thermocouple, the temperature data logger was an Omega four-channel data logger, and the small weather station was a Yuntang YT-QX04 automatic weather station.

[0084] Test results such as Figure 2-6 shown.

[0085] Figure 2-3 The front and cross-sectional SEM images of the fiber array-based radiative cooling surface provided in this embodiment are shown in FIG. As can be seen from the figure, white nylon fibers are uniformly inserted into the bottom glue layer to form an insect hair-like fiber array structure, and the array height is about 500 μm.

[0086] Figure 4 This is the UV-visible-near infrared spectrum of the fiber array-based radiative cooling surface provided in this embodiment. As can be seen from the figure, the surface has a very high reflectivity in the sunlight area, reaching up to 99%, and the average reflectivity in the visible light area is about 97%.

[0087] Figure 5 This is a mid-infrared region emissivity diagram of the fiber array-based radiative cooling surface provided in this embodiment. As can be seen from the figure, the surface has a very low reflectivity in the mid-infrared atmospheric window region. According to Kirchhoff's radiation law, the surface also has a very high (average of more than 95%) mid-infrared emissivity.

[0088] Figure 6This is a graph of the outdoor measured temperature drop of the fiber array-based radiation cooling surface provided in this embodiment. It can be seen from the figure that the surface cooling temperature drop is proportional to the real-time solar radiation intensity. The higher the solar radiation intensity, the greater the temperature drop and the better the cooling effect. The surface can achieve a maximum radiation cooling temperature drop of 9°C, which has excellent radiation cooling performance.

[0089] Example 2

[0090] The only difference between this embodiment and embodiment 1 is that the diameter of the rutile TiO2 nanoparticles is 50 nm.

[0091] Example 3

[0092] The only difference between this embodiment and embodiment 1 is that the diameter of the rutile TiO2 nanoparticles is 500 nm.

[0093] Example 4

[0094] The only difference between this embodiment and embodiment 1 is that the mass ratio of rutile TiO2 nanoparticles, silicone rubber and silicone rubber curing agent is 2:10:1.

[0095] Example 5

[0096] The only difference between this embodiment and embodiment 1 is that the mass ratio of rutile TiO2 nanoparticles, silicone rubber and silicone rubber curing agent is 5:10:1.

[0097] Example 6

[0098] The difference between this embodiment and embodiment 1 is that the surface density of the top fiber array structure is 10g / m 2 .

[0099] Example 7

[0100] The difference between this embodiment and embodiment 1 is that the surface density of the top fiber array structure is 60g / m 2 .

[0101] Example 8

[0102] The only difference between this embodiment and embodiment 1 is that the rutile TiO2 nanoparticles are replaced by an equal amount of SiO2 nanoparticles with a diameter of 200 nm.

[0103] Example 9

[0104] The only difference between this embodiment and embodiment 1 is that the rutile TiO2 nanoparticles are replaced by an equal amount of Al2O3 nanoparticles with a diameter of 300 nm.

[0105] Example 10

[0106] The only difference between this embodiment and embodiment 1 is that the rutile TiO2 nanoparticles are replaced by an equal amount of BaSO4 nanoparticles with a diameter of 200 nm.

[0107] Comparative Example 1

[0108] The only difference between this comparative example and Example 1 is that the raw material for preparing the bottom glue layer does not include rutile TiO2 nanoparticles.

[0109] Comparative Example 2

[0110] The only difference between this comparative example and Example 1 is that the top fiber array structure in the radiation cooling surface is removed, that is, the bottom glue layer is directly solidified without going through the electrostatic flocking process.

[0111] The same method as in Example 1 was used to perform performance tests on the radiation cooling surfaces of Examples 2-10 and Comparative Examples 1-2. The performance test results are shown in Table 1.

[0112] Table 1

[0113]

[0114]

[0115] It can be seen from Table 1 that the mid-infrared region emissivity of Examples 2 and 3 is similar to that of Example 1, and both have excellent infrared emission capabilities; however, the average sunlight reflectivity of Examples 2 and 3 is lower than that of Example 1. This is because the diameter of the rutile TiO2 in Example 2 is too small, and the diameter of the rutile TiO2 in Example 3 is too large. According to the Mie scattering theory, if the scattering particle size is too large or too small, the peak of the scattering efficiency cannot be obtained in the band with the highest solar radiation intensity. Therefore, its sunlight reflection performance is not as good as that of Example 1, which leads to its radiation cooling performance being not as good as that of Example 1.

[0116] The sunlight reflectivity in Example 4 is lower than that in Example 1, because too little TiO2 is added, and the sunlight cannot be effectively reflected; the infrared atmospheric window area emissivity in Example 5 is lower than that in Example 1, because too much TiO2 is added, the glue is too viscous, and the fibers are difficult to insert into the glue layer during the flocking process, and the fibers fall over severely. Therefore, the amount of TiO2 added should be TiO2: silicone rubber = 3:10-4:10 to ensure high reflection of sunlight while achieving good flocking morphology, which has the best technical effect.

[0117] The infrared emissivity of Example 6 is not as good as that of Example 1. This is because the surface density of the fiber array is too small, the fibers are arranged too sparsely on the adhesive layer, and the array structure cannot form a characteristic size equivalent to the wavelength of mid-infrared light, so it is difficult to effectively improve the surface absorption and emission in the mid-infrared region; the average sunlight reflectivity of Example 7 is lower than that of Example 1. This is because the surface density of the fiber array is too large, the fibers are arranged too densely on the adhesive layer, and most of the sunlight is reflected between the top fibers when it is irradiated on the surface, and the reflectivity of the top fibers is lower than the reflectivity of the bottom surface containing TiO2 particles. Therefore, the surface density of the fiber array is between 20-40g / m 2 Only when the high reflectivity in the sunlight area and the high emissivity in the mid-infrared area are taken into account at the same time, the optimal cooling effect can be achieved.

[0118] The reflectivity of the sunlight region of Comparative Example 1 is much lower than that of Example 1, because there is no Mie scattering effect of TiO2. The emissivity of the infrared region of Comparative Example 2 is much lower than that of Example 1, because there is no fiber array structure on the surface and a gradient refractive index layer cannot be formed. Therefore, the radiative cooling performance of Comparative Examples 1 and 2 is far inferior to that of Example 1.

[0119] It can be seen that the present invention has developed a radiation cooling surface based on a fiber array, which has the characteristics of high reflectivity in the sunlight region, high emissivity in the mid-infrared region, flexibility, and good adhesion to the substrate.

[0120] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the fiber array-based radiation cooling surface and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A radiation cooling surface based on a fiber array, characterized in that: The fiber array-based radiation cooling surface includes a bottom glue layer and a top fiber array structure; The raw materials for preparing the bottom glue layer include a polymer matrix, inorganic filler particles and a curing agent; The inorganic filler particles include any one of Al2O3, rutile TiO2 or BaSO4 or a combination of at least two; The top fiber array structure is composed of white nylon fibers; the diameter of the white nylon fibers is 5-15 μm and the length is 400-600 μm; the surface density of the top fiber array structure is 10-100 g / m 2 ; The method for preparing the fiber array-based radiation cooling surface comprises the following steps: Constructing a top fiber array structure on the bottom glue layer by electrostatic flocking and curing to obtain the fiber array-based radiation cooling surface; The bottom glue layer is prepared by the following method: The polymer matrix, inorganic filler particles and curing agent in the prescribed amount are mixed and dispersed to obtain a mixed liquid, and then the mixed liquid is coated on the substrate to obtain the bottom glue layer.

2. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The polymer matrix includes any one of silicone rubber, epoxy resin or fluorocarbon resin, or a combination of at least two of them.

3. The fiber array-based radiation cooling surface according to claim 2, characterized in that: The polymer matrix is ​​silicone rubber.

4. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The inorganic filler particles are rutile TiO2.

5. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The diameter of the inorganic filler particles is 50-500 nm.

6. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The diameter of the Al2O3 is 200-400nm.

7. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The diameter of the rutile TiO2 is 200-400nm.

8. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The diameter of the BaSO4 is 100-300nm.

9. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The mass ratio of the inorganic filler particles to the matrix is ​​3:10-4:

10.

10. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The mass ratio of the curing agent to the matrix is ​​1:10-2:

10.

11. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The thickness of the bottom glue layer is 50-500 μm.

12. The fiber array-based radiation cooling surface according to claim 11, characterized in that: The thickness of the bottom glue layer is 100-200 μm.

13. The fiber array-based radiation cooling surface according to claim 1, characterized in that: The surface density of the top fiber array structure is 20-40 g / m 2 .

14. The method for preparing a fiber array-based radiation cooling surface according to any one of claims 1 to 13, characterized in that: The preparation method comprises the following steps: Constructing a top fiber array structure on the bottom glue layer by electrostatic flocking and curing to obtain the fiber array-based radiation cooling surface; The bottom glue layer is prepared by the following method: The polymer matrix, inorganic filler particles and curing agent in the prescribed amount are mixed and dispersed to obtain a mixed liquid, and then the mixed liquid is coated on the substrate to obtain the bottom glue layer.

15. The preparation method according to claim 14, characterized in that: The mixing and dispersing is vacuum degassing and stirring.

16. The preparation method according to claim 15, characterized in that: The specific process of the vacuum degassing and stirring is: stirring at a rate of 500-1000 r / min for 5-10 min under normal pressure, and then stirring at a rate of 1500-2500 r / min for 3-5 min under a vacuum degree of 20-60 kPa.

17. The preparation method according to claim 14, characterized in that: The coating method includes spraying or scraping.

18. The preparation method according to claim 17, characterized in that: The spraying includes spraying with a spray gun with a caliber of 0.3-0.8 mm or a spray pen with a caliber of 0.3-0.8 mm.

19. The preparation method according to claim 17, characterized in that: The scraping coating includes scraping coating with a four-corner coater.

20. The preparation method according to claim 14, characterized in that: The process of constructing the top fiber array structure on the bottom glue layer by electrostatic flocking is as follows: Fix the bottom glue layer on the metal upper plate, disperse the white polymer fibers on the metal lower plate, turn on the DC high-voltage power supply, and the white polymer fibers will rise vertically under the action of the electrostatic field and insert into the bottom glue layer.

21. The preparation method according to claim 20, characterized in that: The distance between the upper electrode plate and the lower electrode plate is 10-30 cm.

22. The preparation method according to claim 20, characterized in that: The voltage of the DC high-voltage power supply is 5-40 kV, and the power-on time is 5-20 s.

23. The preparation method according to claim 14, characterized in that: The curing temperature is 80-100° C. and the curing time is 2-3 hours.

24. Application of the fiber array-based radiation cooling surface according to any one of claims 1 to 13 in refrigeration and temperature reduction.

25. The use according to claim 24, characterized in that The refrigeration and cooling includes at least one of being used for sun protection and cooling of building exterior walls or vehicles, and condensation of outdoor water collection devices.

Citation Information

Patent Citations

  • Antiskid material based on fiber array, and preparation method thereof

    CN110951456A

  • Preparation method of flexible wave-transparent heatproof heat dissipation film

    CN111100610A